Phylogenetic position, morphological data, call, and geographic distribution of the elusive treefrog Ololygon skuki (Hylidae: Hylinae: Scinaxini) - Nascimento, Filipe A.C.; Araujo-Vieira, Katyuscia [UNESP]; Dubeux, Marcos J.M.; Marinho, Pedro [UNESP]; Guedes-Santos, Jhonatan; Roberto, Igor Joventino; Dos Santos, Ednilza Maranhão; Ávila, Robson Waldemar; Pombal, José P.; Faivovich, Julián (Magnolia Press, 2024)
Ololygon skuki is a species of the O. argyreornata group, only known to occur in an Atlantic Forest fragment in the state of Alagoas, Brazil. Current knowledge about this species is restricted to descriptions of both adults and larvae. In this study, we explore the phylogenetic relationships of O. skuki based on molecular data, provide new morphological observations such as the presence of the nuptial pad on Finger III, describe its call, and update its geographic distribution. Our results indicate that O. skuki is the sister taxon of all other lineages of the O. argyreornata group. Furthermore, sequences from a specimen previously identified as O. argyreornata in the municipality of São Sebastião do Passé, state of Bahia, Brazil, were found to be nested among topotypic specimens of O. skuki. This extends the known distribution of this species approximately 425 km southwest from the type locality. The call of O. skuki consists of a long series of 26–34 short squawk-like pulsed notes, lasting 2.8–3.7 seconds, with a dominant frequency of 4,565.0–5,512.5 Hz.
Keywords: APA Catolé; Atlantic Forest; Behavior; Morphology; O. argyreornata group; Phylogeny